2020
DOI: 10.1248/cpb.c19-00975
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Production of Oxo-fatty Acids by Lipoxygenases Is Mediated by the Radical–Radical Dismutation between Fatty Acid Alkoxyl Radicals and Fatty Acid Peroxyl Radicals in Fatty Acid Assembly

Abstract: Oxo-octadecadienoic acids (OxoODEs) act as peroxisome proliferator-activated receptor (PPAR) agonists biologically, and are known to be produced in the lipoxygenase/linoleate system. OxoODEs seem to originate from the linoleate alkoxyl radicals that are generated from (E/Z)-hydroperoxy octadecadienoic acids ((E/Z)-HpODEs) by a pseudoperoxidase reaction that is catalyzed by ferrous lipoxygenase. However, the mechanism underlying the conversion of alkoxyl radical into OxoODE remains obscure. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Content In our previous study, 1) we elucidated that not only linoleate hydroperoxides (13-HpODE and 9-HpODE) but also OxoODEs (13-OxoODE and 9-OxoODE) were produced in the soybean 15-lipoxygenase (1.0 μM)/linoleate (1.0 mM) system through lipoxygenase and pseudoperoxidase reactions, respectively. In this reaction system (40 µL of reaction solution in a polypropylene microtube (inner volume, 0.6 mL)), the dissolved oxygen content in the reaction solution is lowered within a few minutes via the dioxygenation of the linoleate; subsequently, oxygen molecules in the air phase diffuse into the reaction solution.…”
Section: Chromatographic Quantification Of Linoleate Oxidized Species...mentioning
confidence: 98%
See 2 more Smart Citations
“…Content In our previous study, 1) we elucidated that not only linoleate hydroperoxides (13-HpODE and 9-HpODE) but also OxoODEs (13-OxoODE and 9-OxoODE) were produced in the soybean 15-lipoxygenase (1.0 μM)/linoleate (1.0 mM) system through lipoxygenase and pseudoperoxidase reactions, respectively. In this reaction system (40 µL of reaction solution in a polypropylene microtube (inner volume, 0.6 mL)), the dissolved oxygen content in the reaction solution is lowered within a few minutes via the dioxygenation of the linoleate; subsequently, oxygen molecules in the air phase diffuse into the reaction solution.…”
Section: Chromatographic Quantification Of Linoleate Oxidized Species...mentioning
confidence: 98%
“…Thiyl radicals attack the cis-type double bond and reversibly cleave the π-bond, resulting in conversion to a thermodynamically stable trans-type double bond. In our previous study, 1) we revealed that the pseudoperoxidase reaction of ferrous 15-lipoxygenase with hydroperoxy fatty acids as a substrate at a lower oxygen content produces various lipid radical species. If hydrogen polysulfides coexist in this pseu-doperoxidase reaction system, it is likely that the hydrogen polysulfide-derived thiyl radicals convert the trans/cis conjugated diene moiety of the resultant oxidized fatty acids to trans/trans one.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation